2023
DOI: 10.3389/fragi.2023.1192149
|View full text |Cite
|
Sign up to set email alerts
|

Single cell analysis of transcriptome and open chromatin reveals the dynamics of hair follicle stem cell aging

Abstract: Aging is defined as the functional decline of tissues and organisms, leading to many human conditions, such as cancer, neurodegenerative diseases, and hair loss. Although stem cell exhaustion is widely recognized as a hallmark of aging, our understanding of cell state changes–specifically, the dynamics of the transcriptome and open chromatin landscape, and their relationship with aging–remains incomplete. Here we present a longitudinal, single-cell atlas of the transcriptome and open chromatin landscape for ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…When a certain stem cell activator concentration is reached, some HFSCs will be activated, accompanied by the beginning of the anagen phase ( Ji et al, 2021 ) while the remaining HFSCs still maintained quiescence. Activated HFSCs play a role in hair growth and tissue regeneration, exhibiting versatility in response to various external stimuli ( Zhang et al, 2023 ; Shwartz et al, 2020 ). Studies have highlighted the significance of the microenvironment, especially the role of local mechanics in tissue engineering and regeneration.…”
Section: Hfscs In Epidermal Regenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…When a certain stem cell activator concentration is reached, some HFSCs will be activated, accompanied by the beginning of the anagen phase ( Ji et al, 2021 ) while the remaining HFSCs still maintained quiescence. Activated HFSCs play a role in hair growth and tissue regeneration, exhibiting versatility in response to various external stimuli ( Zhang et al, 2023 ; Shwartz et al, 2020 ). Studies have highlighted the significance of the microenvironment, especially the role of local mechanics in tissue engineering and regeneration.…”
Section: Hfscs In Epidermal Regenerationmentioning
confidence: 99%
“…A transcriptomic study on expanded mouse skin reported that epidermal cells serve as crucial effector cells in skin expansion, with epidermal cell proliferation and renewal playing a decisive role in skin regeneration ( Joost et al, 2018 ; Aragona et al, 2020 ). It was observed that expansion upregulates a number of HFSC-associated genes and the possible downstream differentiated cells—epidermal stem cells, including Krt14, Krt24, Cd34, Krt79, Fgf18, Lgr6, and Lgr5 ( Zhang et al, 2023 ; Zhao et al, 2023 ). The epidermal basal cells of keratinocytes comprise epidermal stem cells that express Krt14 as a marker of actively proliferating keratinocytes ( Wiśniewska et al, 2021 ).…”
Section: Mechanisms Of Epidermal Regeneration Induced By Hfscs Under ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Stem cell fate regulation is complex and controlled by a combination of extracellular signals, transcriptional programs and chromatin organization [ 78 , 79 ]. In stem cells, chromatin is generally maintained in a more open and relaxed state, which facilitates the expression of genes necessary for maintaining pluripotency and cellular quiescence, while compaction of the chromatin is associated with differentiation [ 80 , 81 ].…”
Section: Chromatin Imbalance In Aging and Cancermentioning
confidence: 99%